(untitled) (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2023)
Agglutinated foraminiferal taxa from five stratigraphic sections and eightheen small outcrops of Lower Pliocene deposits were quantitatively analyzed for paleoenvironmental purposes. The studied area is located in Piedmont, northwestern Italy, and includes the northeastern Monferrato, the southern margins of the Turin Hill, the Astigiano, the Albese and part of the Langhe. Studied samples were mainly collected in the marine Argille Azzurre (AA) Formation, and cover a time interval ranging from the MPl1 zone to the MPl4a subzone in the Pliocene Mediterranean Foraminiferal Zonation. Most of the agglutinated assemblages are dominated, or exclusively made, by calc-agglutinated infaunal species of elongated tapered or subcylindrical shape, mainly represented by Bigenerina nodosaria and Martinottiella communis. The deep-water infaunal Cylindroclavulina rudis, Eggerella bradyi and Martinottiella perparva characterized the open-sea basinal facies deposited in the central part of the Piedmont region during the earliest Pliocene. These taxa progressively decreased in abundance until to disappear, and were replaced in the upper silty succession by shelf taxa, dominated by Bannerella gibbosa and Textularia aciculata. In particular, T. aciculata showed its highest abundances in infralittoral to shallow circalittoral muddy sediments of probable fluvial origin, widespread in the Astigiano area, and could be suggested as a typical species of shallow marine delta deposits. Among the 42 agglutinated species here determined, Cyclammina cancellata and Reophax scorpiurus were seldom reported in previous works, Ammobaculites agglutinans, Ammoscalaria spp., Cribrostomoides subglobosus subglobosus, Haplophragmoides canariensis, Psammosphaera spp., and Psammolingulina papillosa were not previously found. The occurrence of these rare taxa could be the proxy of particular sea-floor conditions during the MPl3 zone, characterized by a locally active bottom circulation and mesotrophic waters.